INTERPRETATION OF MAQASID SHARIA PRINCIPLES IN THE CONTEXT OF CHILDREN'S BEST INTEREST: To Avoid Dissenting Opinion On Adoption Motives - M. Adib Ridwan Azizy; Rizky Wibowo (MAQASHID, 2026)
The ambiguity of the phrase ‘best interests of the child’ in Article 39 of Law No. 23/2002 on Child Protection is a major source of potential dissenting opinions and disparity of decisions in the context of adoption in Indonesia. The absence of explicit and measurable juridical parameters opens room for subjective interpretation among judges and legal practitioners, hampering legal certainty and optimal protection of children's rights. This research aims to resolve the interpretative dilemma by proposing the interpretation of the Maqasid Sharia principle as a methodological framework. Using a qualitative normative research method with literature study and hermeneutic analysis, this research examines how the lofty goals of Maqasid Sharia particularly hifz al-nafs (preservation of the soul), hifz al-aql (preservation of the intellect), and hifz al-nasl (preservation of offspring) can provide more objective and structured guidance. The results show that the integration of Maqasid Syariah is able to minimise subjectivity, provide more consistent criteria for judges, and bridge positive law with universal benefit values, thereby reducing dissenting opinions and increasing legal certainty and the quality of child protection in adoption decisions.